International classification of functioning, disability, and health (Classification, Assessment, Surveys and Terminology Team, World Health Organization, 2001)
This CD-ROM includes the International Classification of Functioning, Disability and Health (ICF) in 6 official WHO languages. The ICF classification is to provide a unified and standard language and framework for the description of health and health-related states. It defines components of health and some health-related components of well-being (such as education and labour)